Welcome message from the chairs - Paech, Barbara (2017 IEEE 25th International Requirements Engineering Conference, 2017)
Presents the introductory welcome message from the conference proceedings. May include the conference officers' congratulations to all involved with the conference event and publication of the proceedings record.
Gesehen am 13.12.2019